Implementasi Pengelolaan Zakat dalam Pengembangan Modal Usaha (Studi pada BAZNAS Kota Payakumbuh) - Hafizzullah Hafizzullah; Fatihah Rizki (ZAWA: Management of Zakat and Waqf Journal, 2023)
Payakumbuh City BAZNAS Strategy in determining mustahik candidates who are ┬á┬ágiven productive program assistance: setting goals and targets, announcing prospective mustahik beneficiaries, criteria for mustahik who will be given assistance, the form of business that will be given assistance, the process of announcing┬á businesses, the administration that will have to be completed, receiving and selecting mustahik prospective recipients of assistance, announcing mustahik prospective recipients who pass and determining the nominal amount of assistance. The results of the research that the researchers conducted showed that the Payakumbuh City BAZNAS stipulated requirements and procedures for determining mustahik candidates and carried out a series of activities in monitoring efforts in an effort to┬á activate the misuse of aid. So as a whole what is meant by the title above is that the author will describe the success or failure of productive businesses/business capital at BAZNAS Payakumbuh City in distributing zakat annually.